The impact of exposure to tobacco smoking and maternal trauma in fetal life on risk of migraine - Kobus, Magdalena; Sitek, Aneta; Antoszewski, Bogusław; Rożniecki, Jacek J.; Pełka, Jacek; Żądzińska, Elżbieta (Frontiers in Neuroscience, 2023)
Introduction: Prenatal period is the key time in human development. Many prenatal factors are well-known and largely impact diseases’ origin after birth. Few studies indicated the link between the prenatal period and the prevalence of migraine in childhood and adolescence so far. We decided to broaden current knowledge and investigate whether the prenatal factors influence the prevalence of migraine in adulthood. The objective of this study is to provide an evidence of relationship between in utero environment and risk of migraine. Methods: In total 266 females (136 in the migraine group, 130 in the control group) and 80 males (35 in the migraine group, 45 in the control group), aged 18 - 65 participated in the study. The quality of prenatal environment was characterised on the basis of mother’s and father’s education, tobacco smoke exposure, alcohol consumption and traumatic event during pregnancy, considered as prenatal factors which have the impact on foetal development. Results: Migraine occurrence in adulthood was significantly associated with maternal tobacco smoking during pregnancy (OR 4.00, 95 % CI 1.64-9.74, p = 0.002), traumatic event during pregnancy (OR 2.16, 95 % CI 1.08-4.30, p = 0.029) and positive family history of migraine (OR 18.77, 95 % CI 9.75-36.11, p < 0.001). Discussion: Our study suggests that the foetal programming effect of tobacco smoking exposure and maternal trauma is not limited to prenatal life but extends into adulthood. Our findings support evidence that migraine in adulthood can be partly influenced by early life conditions.